Effects of silodosin on bladder activity in rats with frequent urination induced by pelvic venous congestion. (14th July 2016) - Sugaya, Kimio; Nishijima, Saori; Kadekawa, Katsumi; Ashitomi, Katsuhiro; Ueda, Tomoyuki; Yamamoto, Hideyuki
Abstract : Objective: To examine the effects of silodosin on bladder activity using female rats with frequent urination induced by pelvic venous congestion. Methods: A total of 24 female rats were divided into three groups: sham, pelvic venous congestion and pelvic venous congestion/silodosin group. Rats in the pelvic venous congestion and pelvic venous congestion/silodosin groups were anesthetized with isoflurane, after which the bilateral common iliac veins and uterine veins were ligated. In the pelvic venous congestion/silodosin group, silodosin (0.3 mg/kg/day) was given using an osmotic pump implanted into the subcutaneous space of the back. After 5–6 weeks, analysis of voiding behavior, measurements of urinary 8‐hydroxydeoxyguanosine and nitric oxide metabolites, continuous cystometry under urethane anesthesia, and Evans blue dye extravasation test of the bladder were carried out. Results: In comparison with sham rats, pelvic venous congestion rats showed an increase in urination frequency with a concomitant increase in urine volume, a shorter interval between bladder contractions on continuous cystometry, an increase in urinary 8‐hydroxydeoxyguanosine, a decrease in urinary nitric oxide metabolites and an increase in vesical vascular permeability. In comparison with pelvic venous congestion rats, pelvic venous congestion/silodosin rats showed a decrease in urination frequency with a concomitant decrease in urine volume, a lower maximum bladder contraction pressure, a longer interval between bladder contractions, an increase in urinary nitric oxide metabolites and a decrease in vascular permeability. Conclusion: Silodosin might improve both bladder dysfunction caused by pelvic venous congestion, and the pelvic venous congestion itself.